KENAKALAN REMAJA AKIBAT KELOMPOK PERTEMANAN SISWA - Malihah, Elly (Faculty of Social Science, Universitas Negeri Semarang, 2014)
Hopeteenageras the future generation that determines the fate of the nationin the future seems contrary to the reality of the matterat this time. Delinquency anddeviant behavior among young people today tendre ache salarming point. This is because teensare lessselective in choosinga group of friends that they're in, and come running norm screated by the group it self without referring to the prevailing normsin general. The purpose of this study to determine the cause of the friendship groups of students have an influence in triggering the occurrence of acts of juvenile delinquency. This study use sa case study with a qualitative approach. Using interview sandobservation asa data collection tool to there searc her who conducted the study informants. From there search that has Juvenile Delinquency, Friendship Group of Students.been done can the result sobtained, that adole scents will comply with the normsand behavior of a friendship group because he is getting the benefit sof the group and will be punished if it does not run the norms and group behavior.